Diaspora Tourism: Perspective of Cameroonians living in Famagusta - Akabum, Joyce Agbor Ebob (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This research investigated the reasons why Famagusta based Cameroonians visit their country of origin, dwelling on their motives for traveling, how it feels in their homeland relative to their residing country. This research employed a qualitative technique to analyze its data via an interview guide of open-ended questions with 15 interviewees. Interpretation of data from the interviews showed that the key reasons for diaspora tourists to travel home were mainly visiting friends and family, spending time with loved ones, at festivals or on vacations. There were different reasons for respondents to immigrate to the TRNC, ranging from educational, economic, greener pastures, transit and marriage. The Cameroonian diaspora also bring goods and presents from abroad to deliver in Cameroon to loved ones, carry stuff from Cameroon to bring to the TRNC. The results of the study showed that diasporic tourism is indeed a process by which people should be able to better their lives in their residing country with the lives of their relatives home, notably by sending remittances. Keywords: Diaspora tourism, Diaspora, Tourism.

ÖZ:Bu araştırma, Gazimağusa’da yerleşik olan Kamerunluların menşe ülkelerini neden ziyaret ettiklerine ilişkin sebepler araştırıldı. Bu sebepler; Anayurtlarına seyahat etme motivasyonlarını ortaya çıkarmak ve şu anda yerleşik oldukları ülkede ve anayurtlarında neler hissettiklerini anlamaktır. Bu çalışmada, 15 görüşmeci örneklem büyüklüğünde açık uçlu sorulardan oluşan bir görüşme kılavuzu aracılığıyla verileri analiz etmek için nitel bir araştırma yaklaşımı kullanılmıştır. Yapılan görüşmelerden elde edilen verileri sonuçlarına göre, gurbetçi turistlerin evlerine seyahat etmesinin başlıca nedenleri daha çok arkadaşlarını ve ailelerini ziyaret etmek, sevdikleriyle vakit geçirmek, festivallerde veya tatillerde olmak olduğunu gösterdi. Katılımcıların KKTC'ye göç etmesinin eğitimsel, ekonomik, daha iyi olanaklar, taşınma ve evlilik gibi farklı nedenleri de vardı. Kamerun diasporası yaşadıkları ülkeden ana vatanlarına gelirken sevdiklerine hediyeler ve bazı eşyalar getirirler, geri dönerken ise yaşadıkları yerlere hediyeler götürürler. Bu çalışmanın sonuçları, diaspora turizminin, bireylerin ikamet ettikleri ülkedeki ailelerinin hayatlarını, özellikle para göndererek, daha iyi hale getirebilecekleri bir süreç olduğunu gösterdi. Anahtar kelimeler: Diaspora turizmi, Diaspora, Turizm.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Supervisor: Asst. Prof. Dr. İlkay Yorgancı.
Keywords: Tourism-Diaspora Tourism-Cameroonians-Famagusta-Cyprus (Turkish Republic of Northern Cyprus, 1983-)-Cameroon; Tourism-Social aspects-Heritage Tourism-Diaspora; Travelers-Attitudes-Emigration and immigration-Diaspora Tourist-Identity (Psychology); Diaspora tourism; Diaspora; Tourism; Tourism